SIFAT PEMESINAN EMPAT JENIS KAYU KURANG DIKENAL DAN HUBUNGANNYA DENGAN BERAT JENIS SERTA UKURAN PORI - Achmad Supriadi; Osly Rachman (Jurnal Penelitian Hasil Hutan, 2002)
The machining properties of four lesser known wood species from natural forest in Kalimantan has been investigated. The wood species were gading (Koilodepes sp.), penjalin (Drypetes sp.), arang (Diospyros macrophylla B.) and sibau (Blumeodendron kurzii I.I Sm) with their specific gravities, i.e. 0.83, 0.81, 0.55, and 0.56, respectively. Further, assessment was conducted on the relation between wood characteristics (i.e. specificgravity and vessel diameters) and the possible occurrence of defect due to machining. The machining work included planning, shaping, boring, turning and sanding.The results revealed that machining properties were significantly affected by wood specific and vessel diameter. The higher the specific gravity and the smaller the pore diameter, the less defect that resulted from wood machining. As such, the machining quality of gading and penjalin woods was regarded as very good. Meanwhile, the machining qualities of arang and sibau woods as good to very good. Therefore, to infer, wood with higher specific gravity tends to improve machining properties. Likewise, wood with larger vessel diameter will downgrade the machining properties.